Análise da cointegração e causalidade entre variáveis macroeconômicas e o índice de rentabilidade do mercado brasileiro de imóveis comerciais – IGMI-C - Vasconcelos, José Ananias Tomáz (2017)
The objective of this work was to analyze the causality and cointegration relationship between some macroeconomic variables (family consumption, gross physical capital formation, government consumption, exports and imports), two indicators of national accounting that reflect the real side of the economy (the average exchange rate of the commercial dollar - closing and the average SELIC over rate) and the profitability index of the Brazilian commercial property market (IMGI-C), trying to explain this one. The period of analysis covered time series of quarterly periodicity, starting in the first quarter of 2000 to the second quarter of 2016, making a total of 63 observations of each variable. Therefore, we analyzed the stationarity and lags of the series, as well as the Johansen and Granger causality tests, adopting the Auto-regressive vector model with error correction mechanism - VECM. In this way, it was verified that the performance of the real estate sector seems to be positively correlated with the consumption of the families, exchange rate factor, exports and gross formation of physical capital and negatively with the rate of interest and expenses of the government. In the causality analysis, it was verified that consumption and gross capital formation help explain the IGMI-C.